Particle eh as an Irony Marker in the Indonesian Language: A Corpus-based Study of the Discourse of Blogs - hyunisa rahmanadia (Masyarakat Linguistik Indonesia, 2022)
AbstractThe particle eh in the Indonesian language has a primary function that needs to be explored. One of the unique functions is contributing to ironical utterances as an irony marker. This paper aims to show that the particle eh as an irony marker helps the hearer interpret the utterance. In understanding the particle functions, a corpus-based study has been conducted. Research data is taken from the Indonesian Web Corpus that is accessed from the Sketch Engine platform. Two hundred random samples are collected from this corpus and analyzed qualitatively using interpretative language analysis from the relevance theory perspective. The corpus is a collection of many blogs written in the Indonesian language on various topics. The results show four categories of the particle eh functions in general: initiating self-repair, indicating unexpected events, as an exclamation, and initiating topic changes. Some evidence that particle eh is used to indicate irony is also provided.Â